A kinetics study on cumene oxidation catalyzed by carbon nanotubes: Effect of N-doping. (23rd February 2018) - Mu, Chunlin; Cao, Yonghai; Wang, Hongjuan; Yu, Hao; Peng, Feng
Graphical abstract: Highlights: A kinetics model containing 7 major elementary steps was developed. Decomposition of CHP was the rate-determine step of the cumene oxidation. Nitrogen doping reduces the activation energy of CHP decomposition. Nitrogen doping strengthens the interactions between O2, RO, RO2 and carbons. Abstract: Selective oxidation of hydrocarbons is of great industrial importance. Nanocarbons are recently found highly active for the aerobic oxidation of cumene. In this work, a detailed kinetics study of cumene oxidation catalyzed by carbon nanotubes (CNTs) and nitrogen doped CNTs (NCNTs) was carried out to disclose the crucial influence of N doping in the cumene oxidation. A kinetics model based on the radical reaction mechanism of cumene oxidation was developed, which contained 7 major elementary steps. The kinetics parameters of cumene oxidation upon CNTs and N-doped CNTs (NCNTs) were obtained by the non-linear aggression of the experimental concentration–time data. Mechanistic insights into the effect of N-doping on carbon catalysis were achieved by comparing the kinetics parameters of CNTs and NCNTs. The decomposition of ROOH was found to be the rate-determine step of the cumene oxidation. The nitrogen doping could reduce the activation energy of CHP decomposition, thereby could remarkably accelerate the overall reaction rate of cumene oxidation. The nitrogen doping could also strengthen the interactions between O2, RO, RO2 and the carbon catalysts. Hence, the selectivities to acetophenone and 2-benzyl-2-propanol were improved. This study provides the insight towards the catalytic role of N dopants in the aerobic oxidation of cumene.